Impact of Pesticide Exposure on High-Frequency Auditory Thresholds and Cochlear Function in Young People Residing near Agricultural Areas - Felipe Munoz; Cristian Aedo-Sanchez; Felipe Paredes-Aravena; Enzo Aguilar-Vidal; Pedro Jilberto-Vergara; Gonzalo Terreros (Toxics)
Pesticide exposure poses a significant health risk, with emerging evidence suggesting its impact on auditory function. This study investigated the effects of pesticide exposure on hearing in young rural residents living near agricultural areas in Chile’s O’Higgins Region. We evaluated 51 participants (31 exposed, 20 unexposed) aged 18–35 years, using comprehensive audiological assessments including high-frequency audiometry, distortion product otoacoustic emissions (DPOAEs), and auditory brainstem responses (ABR). Participants were classified based on residential proximity to agricultural areas, with exposed individuals living around 400 m or less from monoculture fields. Results revealed significant differences in high-frequency hearing thresholds (14 and 16 kHz) in exposed individuals. The exposed group showed a higher number of absent DPOAEs and reduced ABR wave V amplitude in the right ear compared to the unexposed group. Additionally, the wave V/I ratio was significantly lower in exposed individuals. These findings suggest that pesticide exposure, even without direct occupational contact, may induce measurable changes in auditory function, particularly affecting high-frequency hearing and neural responses. These results emphasize the need for enhanced monitoring and protective measures for populations residing near agricultural areas where pesticides are extensively used.